Предмет:
Другие предметыАвтор:
анонимПереведем значение выражения (x^2 - x * y - y^2) * (x + y) на многочлен.
(x^2 - x * y - y^2) * (x + y) = x^2 * x + x^2 * y - x * y * x - x * y * y - y^2 * x - y^2 * y = x^3 + x^2 * y - x^2 * y - x * y^2 - x * y^2 - y^3 = x^3 - x * y^2 - x * y^2 - y^3 = x^3 - 2 * x * y^2 - y^3;
В итоге получили, (x^2 - x * y - y^2) * (x + y) = x^3 - 2 * x * y^2 - y^3.
Автор:
fletcherДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть